The brain rhythms of cognition : investigating the dynamics of cortical plasticity through behavioural analysis and MEG - Julia Ericson (2025)
Visuospatial processing is a fundamental cognitive capacity that underlies functions ranging from eye movements to working memory and even mathematical reasoning. Training visuospatial working memory can enhance performance across many cognitive domains — a phenomenon known as cognitive transfer. Although this effect is well established and holds therapeutic promise, the mechanisms driving transfer remain poorly understood. Measuring transfer is also challenging, as improvements during training may arise from multiple intertwined cognitive processes, as well as task-specific learning that does not generalise.The aim of this thesis was to understand how and why visuospatial working memory training produces cognitive transfer. To this end, we developed methods for quantifying transferable improvements and related these behavioural changes to underlying neural dynamics.To address how, we first combined a large behavioural dataset from an online cognitive training platform with dense longitudinal Magnetoencephalography (MEG) recordings in four participants. In Study 1, behavioural analyses revealed that task-specific gains appeared early in training, whereas transferable improvements accumulated gradually and consistently over time. In Study 2, MEG data showed that transfer was accompanied by a progressive, linear increase in alpha (~ 10 Hz) synchronisation within the dorsal attention network — a spatially selective network central to top-down control.To address why, we analysed the longitudinal MEG cohort alongside data from 83 participants in the Human Connectome Project (HCP). In Study 3, we found that dorsal alpha oscillations were tightly linked to the maintenance of visuospatial information. Using a whole-brain computational model in which low-frequency oscillations modulated high-frequency neural activity, we specifically demonstrated that alpha synchronisation could facilitate information routing in the dorsal attention network.Interestingly, the dorsal alpha network was active during the maintenance of non-spatial information as well. This suggests that the network supports a more general neural state of cognitive stability. Such mechanisms offer a compelling explanation for how training-induced neural plasticity can extend beyond visuospatial abilities, leading to broader improvements in attention and general cognitive function — even over relatively short training periods.List of scientific papersI. Ericson, J., & Klingberg, T. (2023). A dual-process model for cognitive training. Npj science of learning, 8(1), 12. https://doi.org/10.1038/s41539-023-00161-2II. Ericson, J., Palva, S., Palva, M., & Klingberg, T. (2024). Strengthening of alpha synchronization is a neural correlate of cognitive transfer. Cerebral Cortex, 34(2), bhad527. https://doi.org/10.1093/cercor/bhad527III. Ericson, J., Ruiz Ibáñez, N., Lundqvist, M., & Klingberg, T. (2025). Low frequency oscillations - neural correlates of stability and flexibility in cognition. Nature Communications, 16(1), 5381. https://doi.org/10.1038/s41467-025-60821-2